The Effect of Principal Transformational Leadership on Teacher Performance to Improve Student Achievement: A Literature Review - Fajar Ahmad Ginanjar; Hasan Hariri; Sowiyah Sowiyah; Riswanti Rini (Universitas Muhammadiyah Enrekang, 2024)
Abstract The importance of school principal transformational leadership and its influence on teacher performance to improve student achievement attracted researchers to investigate it and this article discusses the results of a literature review conducted by the author. There are several articles reviewing the influence of school principals' transformational leadership on teacher performance to improve student achievement, especially in world contexts that can be found. The purpose of this review is to determine the influence of the transformational leadership of school principals on teacher performance to improve student achievement in the world context. Based on the results of a review of literature from various countries in the world, the authors found that the majority of school principal transformational leadership had a positive and significant influence on teacher performance for student achievement. Keywords: transformational leadership; principal; teacher performance; student achievement